Multimedia content encryption techniques and applications - Lian, Shiguo. (CRC Press, 2009)
Presents the research on multimedia content encryption. This book begins with a brief history and then examines performance requirements and fundamental encrypting techniques. It discusses the common techniques of complete, partial, and compression-combined encryption, and also reviews watermarking and joint fingerprint embedding and decryption.